A comparison of assays for the detection of Cryptosporidium parvum in the feces of scouring calves. (March 2022) - Atwal, Harveen K.; Zabek, Erin; Bidulka, Julie; DuCharme, Alecia; Pawlik, Michael; Himsworth, Chelsea G.
Cryptosporidium parvum is a zoonotic, protozoan parasite that causes potentially life-threatening diarrhea in the host and can be transmitted via the fecal-oral route. C. parvum can infect cattle and may be detected in their feces using a variety of tests. We compared the level of agreement, ease of procedure, and cost among PCR, lateral flow immunoassay, fluorescent antibody, and Kinyoun acid-fast stain direct smear tests. Over the course of 9 mo, 74 calf fecal samples were submitted and tested for C. parvum using all 4 tests. A Fleiss kappa value of 0.813 was obtained, indicating an excellent level of agreement among tests. Overall, the best test based on cost and ease of procedure was the Kinyoun acid-fast stain direct smear.